2021
DOI: 10.1007/s10916-021-01721-y
|View full text |Cite
|
Sign up to set email alerts
|

Practice in Information Technology Support for Fangcang Shelter Hospital during COVID-19 Epidemic in Wuhan, China

Abstract: In confronting the sudden epidemic of COVID-19, China and other countries have been under great deal of pressure to block virus transmission and reduce death cases. Fangcang shelter hospital, which is converted from large-scale public venue, is proposed and proven to be an effective way for administering medical care and social isolation. This paper presents the practice in information technology support for a Fangcang shelter hospital in Wuhan, China. The experiences include the deployment strategy of IT infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Along with material availability, the results emphasize the need for efficient supporting services such as IT support, mechanical and electric maintenance, accessibility, etc. Indeed, few studies have identified the latter themes in their findings or chosen these issues as a research topic but those who did have pointed out the importance of a proactive IT Department with a clear strategy (29) and the urgent need to improve interoperability and intuitive user interfaces (30). As part of the healthcare process, support services such as maintenance have the potential to markedly improve patient care when they are immediately available, sensitive to ongoing care priorities and complement an interdisciplinary environment.…”
Section: Discussionmentioning
confidence: 99%
“…Along with material availability, the results emphasize the need for efficient supporting services such as IT support, mechanical and electric maintenance, accessibility, etc. Indeed, few studies have identified the latter themes in their findings or chosen these issues as a research topic but those who did have pointed out the importance of a proactive IT Department with a clear strategy (29) and the urgent need to improve interoperability and intuitive user interfaces (30). As part of the healthcare process, support services such as maintenance have the potential to markedly improve patient care when they are immediately available, sensitive to ongoing care priorities and complement an interdisciplinary environment.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have focused on the spread of COVID-19 in both macro-scale and micro-scale spaces by Anylogic. Though there were some similar micro-scale studies [46][47][48], all of these were based on an ideal experimental environment. With a relatively lack of practicality and few number of experimental simulations, the conclusions are of some contingency.…”
Section: Discussionmentioning
confidence: 99%
“…The information technology support not only improves the work efficiency of the medical staff, but also reduces the risk of cross-infection in hospitals ( 46 ). In the case of a pandemic, several aspects can be improved by using state-of-the-art technology ( 47 , 48 ).…”
Section: Management Of Mobile Cabin Hospitalsmentioning
confidence: 99%